Hubungan Kemandirian Belajar dengan Hasil Belajar Kelas IV A SDN Sendangmulyo 02 - Faradila Indah Megawati; Ikha Listyarini; Husni Wakhyudin; Suherni Suherni (Journal on Education, 2023)
The research aims to examine and to describe independent learning by using learning outcomes of 4th grade in SDN Sendangmulyo 02, Tembalang District, Semarang City. The researcher used a quantitative correlation research to analyze the data. The data were taken from 28 students of 4th grade in SDN Sendangmulyo 02. Sampling technique that the researcher used is a saturation sampling technique. The researcher collected the data through sampling i.e questionnaire and documentation as a main source. The data were analyzed using descriptive statistical analysis, simple correlation analysis, significant test, and coefficient of determination. Based on the results, it can be stated as follow there is a positive and significance relationship between independent learning and learning outcomes and it categorized as a strong relationship.